The development and evaluation of an automated multimedia kiosk-based visitor survey system in Iguaçu National Park, Brazil - Nobre, Ismael, author; Wallace, George N., advisor; Rolston, Holmes, 1932-2025, committee member; Vaske, Jerry J., 1951-, committee member; Newman, Peter, 1972-, committee member (Colorado State University. Libraries, 2011)
The Brazilian system of parks and related areas has shown a continued increase in geographic area and in recreational use demands. The federal government recently established policies aimed at improving visitor management and setting standards for public visitation to the nation's protected area (PA) system - a major shift from the era where visitors were seen as burdensome to conservationists. New policies require the collection of visitor information to inform improvements to the visitor experience and other management actions. Brazilian PA managers, however, have a limited data base, limited experience and few resources for undertaking visitor studies. Accordingly, this research developed and evaluated an automated visitor interviewing system to help close this information gap. The system developed and integrated custom-made software and hardware capable of collecting multidimensional survey data, including cognitive data, environmental variables, and the affective state of respondents. The kiosk system utilizes an animated virtual host as part of a machine-human communication strategy aimed at intertwining the survey system with the park experience. The multimedia design reduces the respondent burden and enables the evaluation of current or future physical, social and managerial settings using virtual reality depictions. A variety of features reduces the administrative burden for managers. The development and use of the kiosk are described in detail. The prototype survey station was tested in Iguaçu National Park, Brazil, between January and December of 2008 yielding a sample size of 4,047 respondents. The study evaluated the ability of an unhosted station to collect good visitor information and the time and effort visitors spent answering the questionnaire and interacting with the survey station. It also assessed how environmental variables like weather or river flow, (also measured by the station), affected visitor satisfaction. The study found among other results that the survey station operating in either a hosted or unhosted mode, produced the same results; that 54.8% of respondents were committed to answering to all questions, 26% were partially committed and 19.1% were uncommitted; and verified that environmental variables did affect overall visitor satisfaction.